Two Synchronous Neonatal Tumors: An Extremely Rare Case - M. Rodríguez-Zubieta; K. Albarenque; C. Lagues; A. San Roman; M. Varela; D. Russo; G. Podesta; D. Steinberg; C. Schauvinhold; A. Etchegaray; M. T. G. de Dávila (Case Reports in Pathology)
We report a case of a newborn with two synchronous tumors—sialoblastoma and hepatoblastoma—diagnosed at 20 weeks of gestation by magnetic resonance imaging (MRI) and ultrasonography (US). The aim of this study was to describe the management of this case together with a review of the literature. Our patient had a large facial tumor associated with extremely high alpha-fetoprotein levels. Diagnosis of the tumors was made by surgical biopsy, showing typical features in both. Sialoblastoma is a potentially aggressive tumor. In our case, the Ki67 index in the sialoblastoma was between 20 and 30%, indicating a possibly unfavorable behavior. The infant underwent surgery and chemotherapy in different steps. Complete surgical resection with clean margins is considered to be the best treatment option for sialoblastoma. Only four similar cases were previously reported. Timely management by a multidisciplinary team is essential in these difficult cases. In our patient, outcome was good at the time of this report.